Mutational Landscape and Evolutionary Pattern of Liver and Brain Metastasis in Lung Adenocarcinoma - Jiang, Tao; Fang, Zhaoyuan; Tang, Shijie; Cheng, Ruirui; Li, Yanan; Ren, Shengxiang; Su, Chunxia; Min, Weijie; Guo, Xianchao; Zhu, Wei; Zhang, Henghui; Hou, Likun; et al. (Journal of thoracic oncology, 2021)
A comprehensive genomic analysis of paired primary tumors and their metastatic lesions may provide new insights into the biology of metastatic processes and therefore guide the development of novel strategies for intervention. To date, our knowledge of the genetic divergence and phylogenetic relationships among diverse metastatic lesions from cancer remains limited. We performed whole-exome sequencing in 84 tissue and blood samples from 26 patients with lung adenocarcinoma having liver metastases (LiM) or brain metastases (BrM) before any systemic therapy, with the goal to molecularly characterize the metastatic process. Mutational landscape and evolutionary patterns were compared between paired primary lesions (primary lesion of LiM or BrM) and metastases (metastatic site of LiM or BrM). We found that common driver mutations, including TP53 and EGFR, were highly consistent between paired primary and metastatic tumors. Although tumor mutational burden was comparable among groups, the LiM group had significantly higher mutational and copy number variational similarity than the BrM group between paired primary lesions and metastases (p = 0.019 and p = 0.035, respectively). Phylogenetic analysis further revealed that LiM-competent disseminations had a higher level of genetic similarity to their paired primary lesions and were genetically diverged from their primary tumors at a relatively later stage than those of BrM. These results suggest that LiM favorably followed the linear progression model, whereas BrM was more consistent with the parallel progression model. This study suggests that the mutational landscape and evolutionary pattern was distinctly different between the LiM and BrM of lung adenocarcinoma.